Freedom of Religion in post-secular Australia1. (September 2021) - Possamai, Adam; Possamai-Inesedy, Alphia
Habermas coined the term post-secularism to reflect a time period in which religions are given a more central part in social and political life. Even if there is more openness to religion, many religious groups would claim that Western societies are nevertheless still dominated by secularism and want to ensure that freedom of religion and belief remain protected and promoted. This article explores the recent Australian Religious Freedom Review as a case study of the social tension between freedom for and from religion to argue that we might have moved beyond a post-secular sphere in this country. In this phase, what is meant by freedom of religion has shifted from a focus in having all religious groups being able to freely practice their faith to a focus by some mainstream religions to remain free to discriminate on the basis of their faith.